The Juridical Framework of the Pentahelix Model in the Preparation of Regional Medium-Term Development Planning - Ngesti Dwi Prasetyo; Arrsa, Ria Casmi; Haq, Cendekiawan Ainul; Retno Catur Kusuma Dewi (Magister of Law, Faculty of Law, University of Mataram, 2023)
Regional Development Planning is a process of compiling the stages of activities involving various elements of stakeholders to improve social welfare in an area/region within a certain period. In the provisions of Article 260, Law No.23 of 2014 concerning Regional Government, it is stated that the regions under their authority shall prepare regional development plans as an integral part of the national development planning system. The pentahelix planning model is an alternative to building a participatory and partnership planning framework that emphasizes the partnership principle, that it is necessary to know the urgency of the pentahelix planning model and the pentahelix planning model in the implementation of the regional medium-term development planning (RPJMD) to realize good governance (good governance), with a normative juridical research method with a statute approach, a conceptual approach, and a cross-disciplinary approach to law to solve related problems. The Pentahelix model has five actors who play a role in it, namely academics, business actors, communities, government, and media.